Penggunaan framework odoo untuk mengembangkan module entERPrise resource planning yang lebih efektif - Permatasari, Zulia Nur; Nugraha, Nugraha (Computer Science and Information Technology, 2023)
ERP module development using the Odoo framework has become a major focus in the information technology industry in recent years. Odoo is one of the most popular open-source software platforms for entERPrise resource management (ERP). ERP is an integrated system that helps companies manage and coordinate various business processes, such as finance, logistics, production, and sales. The ERP concept is a system that integrates the processes of each line in the company's management in a transparent and highly accountable manner. In an increasingly complex and rapidly changing business world, Odoo is emerging as a robust and affordable solution for companies to improve operational efficiency, optimize productivity and face stiff competition. The problems faced by the author while carrying out research at PT. Hashmicro Solusi Indonesia includes a client owned by PT. Omicron Creative Solutions has problems related to employee appraisals which are still manual, namely using Microsoft excel and Client from PT. Omicron Creative Solutions Experiencing Difficulties in the Requirement Process Prospective New Employees, the author is involved in a module development project that already existed before. In this project, the author works with an existing development team to develop existing modules in Odoo. So the authors developed the odoo module regarding employee assessment. This research proves that the employee appraisal application at PT. Omicron Creative Solutions uses the odoo module to be more effective.